PERAN BRAND IMAGE MEMEDIASI PENGARUH KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN - Dananjaya, Gusti Nyoman Bagus; Rastini, Ni Made (E-Jurnal Manajemen; Vol 7 No 10 (2018), 2018)
This research aims to explain the effect of product quality on brand image, the effect of product quality on customer loyalty, the influence of brand image on customer loyalty, and the role of brand image to mediate the effect of product quality on customer loyalty of Kober Mie Setan in Denpasar City This research was conducted in Denpasar using 100 respondents. Data collection method used is purposive sampling method with path analysis technique. The results showed that product quality had a positive and significant effect on brand image. Product quality has a positive and significant impact on customer loyalty. Brand image has a positive and significant impact on customer loyalty. Brand image as a mediation variable significantly indirect influence on customer loyalty through product quality variables. Kober Mie Satan needs to pay attention to the portion of food to match the expectations of the consumers. In addition, Kober Mie Satan needs to improve the positive reputation for the image of Kober Mie Satan is considered positive and able to create customer loyalty. Keywords: product quality, brand image, customer loyalty